2010
DOI: 10.1007/s10543-010-0250-z
|View full text |Cite
|
Sign up to set email alerts
|

On high order symmetric and symplectic trigonometrically fitted Runge-Kutta methods with an even number of stages

Abstract: The existence and construction of symplectic 2s-stage variable coefficients Runge-Kutta (RK) methods that integrate exactly IVPs whose solution is a trigonometrical polynomial of order s with a given frequency ω is considered. The resulting methods, that can be considered as trigonometrical collocation methods, are fully implicit, symmetric and symplectic RK methods with variable nodes and coefficients that are even functions of ν = ωh (h is the step size), and for ω → 0 they tend to the conventional RK Gauss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…(iii) The results stated in Lemmas 2.4 and 2.5 indicate that for symmetric FFRK methods there is an important reduction of the fitting conditions (27), and this reduction is collected in the following Corollary 2.6. For an s-stage symmetric FFRK method fitted to a linear space F ⊂ H 1 ∪ H 2 , the fitting conditions (27) …”
Section: Theorem 22 An Rk Methods (2)-(3) For Solving the Hamiltoniamentioning
confidence: 93%
See 3 more Smart Citations
“…(iii) The results stated in Lemmas 2.4 and 2.5 indicate that for symmetric FFRK methods there is an important reduction of the fitting conditions (27), and this reduction is collected in the following Corollary 2.6. For an s-stage symmetric FFRK method fitted to a linear space F ⊂ H 1 ∪ H 2 , the fitting conditions (27) …”
Section: Theorem 22 An Rk Methods (2)-(3) For Solving the Hamiltoniamentioning
confidence: 93%
“…When the frequency used in the exponential fitting process is λ = 0 (z = 0), the new integrators reduce to the standard four-stage eighth-order Gauss integrator. It is shown that such fitted methods are a reliable alternative to the standard four-stage eighth-order Gauss integrator and the trigonometrically fitted four-stage eighth-order STFRK4 code derived in [27] to describe the evolution of some oscillatory problems. Furthermore, the computational cost of the new modified EFRK methods is similar to their counterparts standard RK methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Just as the research of symplectic and EP methods, EF/TF symplectic methods have been studied extensively by many authors (see, e.g. [7,8,9,15,36,37,40]). By contrast, as far as we know, only a few papers paid attention to the EF/TF EP methods (see, e.g.…”
Section: Introductionmentioning
confidence: 99%